(3ebGdI aj HjGf eG hge ajg CHh Ydi Hf GdgjKe aj cJGHg aj GdTchc Ydi EbdjOSs - (3CHh GdaJhM fLe GdOjf CMeO Hf eMeO Hf GdSQj GdHZOGOj, GHf GdUdGM,J (B548 (3g` s
(3ChdgG (B:s
(3bGd Ef ef CKQ GdMb hWdHI JejR eSJHTY YfOg GdJfHjg Ydi GdZdW SjeG ai GdCehQ GdHQgGfjI hGdeWGdH GdJYjfjI hEf YXeJ QJHI GdefHg s
(3BNQgG (B:s
(3aEPkG RGhjI C eSGhjI dRGhjI O hRGhjI L JSGhi RGhjI Q hPdc eG CQOfG Cf fHjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYGTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs